2012
DOI: 10.1016/j.jacc.2012.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cardiovascular Events Are Best Predicted by Low Central/Peripheral Pulse Pressure Amplification But Not by High Blood Pressure Levels in Elderly Nursing Home Subjects

Abstract: In very elderly individuals living in nursing homes, low PPA from central to peripheral arteries strongly predicts mortality and adverse effects. Assessment of this parameter could help in risk estimation and improve diagnostic and therapeutic strategies in very old, polymedicated persons. In contrast, high BP is not associated with higher risk of mortality or major CV events in this population. (Predictive Values of Blood Pressure and Arterial Stiffness in Institutionalized Very Aged Population [PARTAGE]; NCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 27 publications
4
95
0
10
Order By: Relevance
“…22 To our knowledge, this the first study to prospectively indicate an association between OHyperT and strong cardiovascular outcome in a old frail institutionalized population. In a previous study involving this population, we showed higher mortality rates in individuals with lower SBP levels, 23 especially in those receiving >1 antihypertensive medications. 24 However, as shown in Table 3 in the present analysis, the observed overmortality in the OHyperT group persisted even after adjustment for sitting SBP levels.…”
Section: Discussionmentioning
confidence: 46%
“…22 To our knowledge, this the first study to prospectively indicate an association between OHyperT and strong cardiovascular outcome in a old frail institutionalized population. In a previous study involving this population, we showed higher mortality rates in individuals with lower SBP levels, 23 especially in those receiving >1 antihypertensive medications. 24 However, as shown in Table 3 in the present analysis, the observed overmortality in the OHyperT group persisted even after adjustment for sitting SBP levels.…”
Section: Discussionmentioning
confidence: 46%
“…by guest on May 9, 2018 http://circimaging.ahajournals.org/ Downloaded from Blood Pressure and Arterial Load After TAVR afterload associated with an elevated SBP, which would contribute to worse post-TAVR heart failure and survival. Instead, we found that lower, not higher, SBP was associated with worse heart failure-related quality of life and higher cardiovascular and all-cause mortality, and lower SBP was associated with worse LV function at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…The following points are noteworthy: (1) that nocturnal brachial BP has been shown to be the strongest BP parameter as a predictor of clinical outcomes, 3,9 (2) that data are emerging to suggest that central aortic pressure may be a better predictor of target-organ damage and clinical outcomes than its brachial counterpart, [5][6][7] and (3) that data are emerging, implicating an association between reduced PPA and risk for cardiovascular events. 22,26,27 Thus, it is conceivable that nocturnal CASP or CAPP could represent the most important hemodynamic determinant of BP-related cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%